Project-based learning in capstone design courses for engineering students: Factors affecting outcomes - Joo, Young Ju; Lim, Kyu Yon; Lee, So Young (Issues in educational research, 2019)
This study aimed to examine the structural relationships among factors that affect learner satisfaction and achievement in project-based learning for capstone design courses in engineering education. Specifically, problem-solving efficacy, task value, teamwork competency, and task authenticity are suggested as critical factors that affect learner satisfaction and perceived achievement. The study employed structural equation modelling in order to examine the relationships among the variables, and the data from 363 university students who were enrolled in capstone design courses were analysed. The results suggest that task value and task authenticity exerted significant effects on learner satisfaction. Problem-solving efficacy, teamwork competency, task authenticity, and satisfaction exerted significant effects on learning outcomes, but task value did not. The results imply that the effects of problem-solving efficacy on perceived achievement reveal the importance of motivational factors in capstone design courses. In addition, instructional strategies that highlight task utility value and provide environments in which learners can share that value would be meaningful in promoting learning effectiveness in capstone design courses.